Normalisasi Hubungan Jerman dan Yahudi Melalui Penyembuhan Trauma Sejarah dalam Film The Zookeeper’s Wife - Ahdania Asti Erina; Lisda Liyanti (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
This study discusses trauma healing through the film "The Zookeeper's Wife" which was adapted from a novel by Dianne Ackerman and directed by Niki Caro as a way to normalize the relations between Germans and Jews. The purpose of this study was to identify the signs  in the film which can be used as a healing from historical trauma due to the holocaust. This study uses qualitative method with data in the form of data extraction that has been taken from the film "The Zookeeper's Wife." Using Charles Sanders Pierce’s semiotic theory and Trauma theory by some experts, the outcome of this research shows that there are two elements for healing historical trauma, namely the trauma healing of Urszula, a Jewish girl and the trauma healing of German that leads to German-Jewish normalization.